UNDERSTANDING ORGANISATIONAL CAPACITY BUILDING AND ITS INFLUENCE ON FIRM EFFECTIVENESS - Ukandu, Nnenna E.; Monyei, Francis E.; Ukpere, Wilfred I. (Veredas do Direito, 2026)
Organisational development plays a crucial role in enhancing overall organisational effectiveness, yet many organisations face challenges in effectively implementing development initiatives. This study investigated the impact of organisational capacity building on organisational effectiveness, with particular emphasis on indicators such as the incremental change management process. A descriptive survey research design was employed to systematically capture existing conditions without manipulating variables. The study population consisted of 420 employees. Structured questionnaires were used to gather data, which were then verified by professionals and put through the test-retest technique to determine reliability. The results showed coefficients ranging from 0.723 to 0.835. While the data was presented using descriptive statistics, such as frequency tables and percentages, the hypotheses were tested using basic regression analysis. The results showed that managing changes gradually improves organisational effectiveness. The study concludes that organisational development initiatives positively influence overall organisational effectiveness, and investing in employee development, structured change management, and team-building strategies is essential for sustained performance improvement. The study recommends that organisations invest in employee development, structured change management initiatives, performance management systems, and team-building programs to strengthen skills, competencies, and overall organisational effectiveness.